PENGARUH PERSEPSI KUALITAS PRODUK, PERSEPSI HARGA DAN GAYA HIDUP HIJAU TERHADAP MINAT BELI MELALUI CITRA MEREK SEBAGAI VARIABEL INTERVENING PADA KENDARAAN SEPEDA MOTOR LISTRIK DI JAKARTA - Sandi Mega Saputra; Annisa Anindya; Rijal Arslan; Aisyah Tiar Arsyad; Ditha Riyansa (Jurnal Maneksi (Management Ekonomi Dan Akuntansi), 2026)
Introduction: Worsening air pollution and high exhaust emissions from fossil-fueled motor vehicles have become an urgent environmental issue. The use of electric motorcycles is viewed as a solution to reduce those emissions, yet adoption in Indonesia remains low due to factors such as high initial costs, limited charging infrastructure, and a lack of consumer awareness. Methods: A quantitative approach using Partial Least Squares Structural Equation Modeling (PLS-SEM) was employed. Data were collected via a questionnaire distributed to 110 respondents in Jakarta. Data analysis evaluated construct validity and reliability, as well as the relationships among variables in the research model.Results: The findings demonstrate that perceived product quality and perceived price significantly impact brand image, yet do not exert a direct influence on purchase intention. A green lifestyle also significantly affects brand image, yet it does not directly influence purchase intention. Brand image was identified as a significant intervening variable that mediates the relationships among perceived product quality, perceived price, and green lifestyle regarding purchase intention.Conclusion and suggestion: Brand image plays a key role in enhancing purchase intention for electric motorcycles. Therefore, manufacturers are advised to strengthen brand image through effective branding strategies and product quality improvements. This study contributes to the development of marketing strategies for electric motorcycles in Indonesia. Keywords: Brand image, green lifestyle, perceived price, perceived product quality, purchase intention